Housing Subsidies and Early Childhood Development: A Comprehensive Review of Policies and Demonstration Projects. Issue 2 (4th March 2019) - Aratani, Yumiko; Lazzeroni, Sarah; Brooks-Gunn, Jeanne; Hernández, Diana
ABSTRACT: In this article, we ask how housing subsidies might influence young children. We examine two national housing policies – public housing assistance and the Section 8 vouchers program – and two demonstration projects that aimed to improve the administration of providing housing subsidies – HOPE (Homeownership Opportunities for People Everywhere) VI and Moving to Opportunity. This article is a critical examination of these policies and demonstration projects in relation to the following housing dimensions that promote the healthy development of young children: income supplements residential stability, physical environment, access to services and amenities, housing choice, neighborhood safety, and social capital. We compared advantages and limitations of each of these national housing policies and demonstration projects and examined ways in which they might influence children in these housing dimensions. The article concludes with implications and future research directions for U.S. housing policy by discussing its most recent U.S. Department of Housing and Urban Development (HUD) initiative, Rental Assistance Demonstration, in addressing limitations of housing policies and demonstration projects we examined.